The Influence of Corporate Tax Rate Reductions on Foreign Direct Investment (FDI): Evidence from Emerging Markets - Diana Magfiroh (Journal of Taxation Insights Policy Practice, 2025)
This study investigates the impact of corporate tax rate reductions on foreign direct investment (FDI) inflows in emerging markets. The study employs a quantitative approach, using both cross-sectional and panel data analysis, to assess whether lower corporate tax rates significantly increase FDI and to identify other factors that may moderate this relationship. Data from 25 emerging markets are analyzed using purposive sampling. Regression analysis using the Ordinary Least Squares (OLS) method showed a statistically significant relationship between corporate tax reductions and increased FD I inflow (p 0.05). The study identifies several challenges in implementing effective tax reduction policies. The findings highlight the need for a comprehensive approach that goes beyond simple tax cuts.